(untitled) (El-Wahat Journal for Research and Studies, 2026)
This study seeks to provide an overview of the state of mathematical sciences in the Central Maghreb during the 8th–9th centuries AH / 14th–15th centuries AD. The aim is to identify the place of mathematical sciences within scholarly life, as well as the main factors and influences that contributed to their development during this period. Chief among these was the impact of the Andalusian elite who chose the cities of the Central Maghreb as their new home. The scholarly traditions of Tunisia and Morocco also made significant contributions, in addition to the campaign of Abu al-Hasan al-Marini into the Central Maghreb, during which he was accompanied by an army of scholars. As a result, mathematical knowledge in its various branches witnessed a remarkable revival in the urban centers of the Central Maghreb, particularly in Tlemcen. Prominent mathematicians emerged there, such as al-Ābilī, Abū ʿUthmān Saʿīd al-ʿUqbānī, Ibn al-Qunfudh al-Qusanṭīnī, and al-Qalaṣādī, who contributed to the advancement of mathematical knowledge through both teaching and authorship. Their fame extended beyond the Central Maghreb, ensuring the continuity of scholarly and mathematical exchange among the intellectual centers of the Islamic West.